Analisis Kualitas Air Pada Area Kerja Penambangan Bijih Nikel Di Kecamatan Kapontori Kabupaten Buton Provinsi Sulawesi Tenggara: Water Quality Analysis in the Nickel Ore Mining Area, Kapontori District, Buton Regency, Southeast Sulawesi Province - Muhammad Ilham Kadar; Deniyatno; Irfan Saputra; Tri Utomo Taliding; La Ode Miqdad Husein (Journal of Engineering Science and Technology Applications, 2026)
Kapontori District, Buton Regency, Southeast Sulawesi Province" aims to assess water quality conditions surrounding the nickel mining site and identify potential environmental impacts. The study focuses on surface water located in the vicinity of mining operations, utilizing both physical and chemical parameters. The methodology involves water sampling and the subsequent comparison of laboratory test results against the standards set by the Regulation of the Minister of Environment and Forestry Number 05 of 2022. This research is expected to provide insights into actual water quality conditions, identify potential pollution resulting from mining activities, and illustrate the distribution patterns of impacts on surface water and community water sources. Furthermore, the study aims to offer recommendations for environmental management, specifically regarding pollution prevention, acid mine drainage control, and the improvement of mine water management systems. Scientifically, this research contributes to the advancement of knowledge in the fields of mining environment, environmental geochemistry, and mine hydrology. Practically, it provides a foundation for mining companies, local governments, and the community to enhance efforts in managing and protecting water quality in Kapontori District, Buton Regency, Southeast Sulawesi Province